2014
DOI: 10.3389/fenvs.2014.00050
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic contamination in shallow groundwater and agricultural soil of Chakdaha block, West Bengal, India

Abstract: The study area comes in one of the eight districts of West Bengal where groundwater contains arsenic above the prescribed limit by WHO (10 µg/l). Each day groundwater is being withdrawn by the village people for the fulfillment of their basic needs and for agricultural purposes. With the groundwater along with high concentration of arsenic (As), many other heavy metals are also getting introduced in the environment. In the areas with a long history of use of such groundwater, the agricultural lands have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 49 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Inauen et al (2013) found that 21% of all mortality occurred in the As contaminated sub-districts in Bangladesh. Thus, high As contamination could be responsible for high risks of morbidity and mortality in exposed populations (Yu et al, 2003;Kapaj et al, 2006;Flanagan et al, 2012;Shrivastava et al, 2014;Hossain, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inauen et al (2013) found that 21% of all mortality occurred in the As contaminated sub-districts in Bangladesh. Thus, high As contamination could be responsible for high risks of morbidity and mortality in exposed populations (Yu et al, 2003;Kapaj et al, 2006;Flanagan et al, 2012;Shrivastava et al, 2014;Hossain, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure pathways of contaminants may vary from region to region, depending on factors such as human activity, geological composition of the aquifer and more. Also, various climatic and geomorphic conditions such as rainfall, runoff, infiltration rate, groundwater level and fluctuation, groundwater flow pattern, distribution pattern of toxic elements, and many more, can influence exposure pathways (Bhattacharya et al, 2002(Bhattacharya et al, , 2011Shrivastava et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the Bengal Basin, elevated levels of manganese (Mn) and arsenic (As) have adversely impacted groundwater quality, prompting serious concerns to human health (Bhattacharya et al, 1997;Nickson et al, 1998;BGS and DPHE, 2001;Buschmann et al, 2008;Datta et al, 2009Datta et al, , 2011Frisbie et al, 2009;Farooq et al, 2011;Sankar et al, 2014;Datta, 2015;Shrivastava et al, 2015;Kshetrimayum and Hegeu, 2016). Further, groundwater is the primary source of drinking water in many of these regions due to surface waters being contaminated by anthropogenic waste (McArthur et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%